Criminal Liability Of Illegal Firearm Possession Perpetrators Resulting In Death Due To Negligence - Danil Erlangga Mahameru; Abdul Kholiq (PALAR | PAKUAN LAW REVIEW, 2026)
The illegal possession of firearms by civilians, accompanied by careless use resulting in the death of another person, constitutes a criminal law issue demanding precision in the construction of criminal fault. This study examines the criminal liability of a perpetrator whose negligence caused death alongside illegal firearm possession, while also evaluating the application of law and judicial considerations in the Decision of the Gunung Sugih District Court Number 349/Pid.B/2024/PN.Gns and the Decision of the Tanjung Karang High Court Number 13/PID/2025/PT TJK. The novelty of this research lies in its critical analysis of the criminal fault construction employed by the judges, particularly in determining whether the perpetrator's conduct is more appropriately qualified as gross negligence (culpa lata) or conditional intent (dolus eventualis). This study employs a normative juridical method incorporating a statutory approach, a conceptual approach, and a case approach, with a prescriptive-interpretive analytical technique applied to judicial considerations. The findings reveal that the perpetrator's awareness of the illegal and dangerous nature of the firearm used places his mental attitude beyond mere ordinary negligence, thereby conceptually opening the possibility of dolus eventualis qualification. Furthermore, an inconsistency was identified between the legal facts and the fault qualification assigned by both the prosecutor and the judges, as the perpetrator's risk awareness was not fully internalized within the construction of the charges or the decisions. The divergence in sentencing between the two court levels also reflects a paradigmatic disparity in assessing the purposes of punishment. This study recommends reforming firearm regulations to incorporate a more structured gradation of criminal liability, strengthening an integrated firearm ownership oversight system, and developing prescriptive prosecution and sentencing guidelines for similar cases to enhance consistency in law enforcement and the protection of public safety. Keywords: criminal liability; negligence; dolus eventualis; illegal firearms.